Temperature-insensitive Quasi-distributed Fiber-optic Fabry-Perot High-pressure sensing based on microwave interference system. (June 2023) - He, Xiu; He, Zhengxi; Ran, Zengling; Cui, Jianxin; Wang, Nan; Gong, Jiangling; Guo, Jiawei; Xiao, Yanbo; Sun, Dong; Zhu, Jialiang; Li, Zhuoyue; Yu, Yun; et al.
Highlights: A temperature-insensitive quasi-distributed high-pressure test system is proposed. A quasi-distributed fiber-optic sensor formed by PCF based EFPI units is demonstrated. Microwave interference system for spectral reconstruction of cascaded FPI units is achieved. Spectral results gotten by microwave interference system follows results based on OSA. Abstract: A temperature-insensitive quasi-distributed fiber-optic high-pressure sensing technique based on cascaded extrinsic Fabry-Perot (EFP) sensing units and an optical carrier based microwave interference system (OCMI) is proposed and demonstrated. The EFP unit formed by hollow-core photonic bandgap fiber has advantages of low-insertion loss and low temperature–pressure cross sensitivity, and the OCMI system based on a tunable single-wavelength light can simultaneously reconstruct optical interferograms of multiple EFP units. Experimental results show the optical interferograms reconstructions of three cascaded EFP units are well agreement with those using an optical spectrum analyzer. Moreover, the EFP unit has a wide measurement range of 0 ∼ 100 MPa and a low temperature–pressure cross-sensitivity of –0.02 MPa/℃, which can be comparable to that of a point fiber-optic pressure sensor. This technique provides a new idea of high-performance distributed pressure sensing.